Oxidative Protein Folding Promotion by Imidazoyl-conjugated Thiol - Okada, Shunsuke; Matsumoto, Yosuke; Okumura, Masaki; Muraoka, Takahiro (Chemistry letters, 2023)
The promotion of protein folding is an important subject that can contribute to the efficient production of biological medicines. Here we report the promotion of disulfide bond-coupled protein folding by imidazoyl-conjugated thiol (ImdSH). ImdSH accelerated the disulfide bond formation and folding of reduced ribonuclease A and bovine pancreatic trypsin inhibitor relative to glutathione as a conventionally used additive.